Drug resistance in leishmaniasis: current drug-delivery systems and future perspectives. (October 2013) - Yasinzai, Masoom; Khan, Momin; Nadhman, Akhtar; Shahnaz, Gul
Leishmaniasis is a complex of diseases with numerous clinical manifestations for instance harshness from skin lesions to severe disfigurement and chronic systemic infection in the liver and spleen. So far, the most classical leishmaniasis therapy, despite its documented toxicities, remains pentavalent antimonial compounds. The arvailable therapeutic modalities for leishmaniasis are overwhelmed with resistance to leishmaniasis therapy. Mechanisms of classical drug resistance are often related with the lower drug uptake, increased efflux, the faster drug metabolism, drug target modifications and over-expression of drug transporters. The high prevalence of leishmaniasis and the appearance of resistance to classical drugs reveal the demand to develop and explore novel, less toxic, low cost and more promising therapeutic modalities. The review describes the mechanisms of classical drug resistance and potential drug targets in Leishmania infection. Moreover, current drug-delivery systems and future perspectives towards Leishmaniasis treatment are also covered.